Reflecting on the two-way educational exchange between Korea and the United States - Lee, Jae-won (Bodhi: An Interdisciplinary Journal, 2013)
Bodhi: An Interdisciplinary Journal, 5, 2011, Page 132-143 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8048